2018
DOI: 10.5812/msnj.86895
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Selective Oropharyngeal Decontamination Using Topical Antibiotics on Oropharyngeal and Tracheal Colonization in Trauma Patients Admitted to the Intensive Care Units of Zahedan, Iran: A Clinical Trial Study

Abstract: Background: Pneumonia is one of the most common hospital-acquired infections, where 86% is associated with mechanical ventilation, known as ventilator-associated pneumonia (VAP). Oropharyngeal decontamination reduces the incidence of VAP by medicinal agents. Objectives:The aim of the present study was to determine the effect of oropharyngeal decontamination using topical antibiotics on oropharyngeal and tracheal colonization of trauma patients admitted to the intensive care unit (ICU). Methods: The present dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…21,23 Other studies employed this method; the rates of intra-oral bacterial colonization and VAP were found to reduce in all patients. 2,51 In the long-term use of SOD, most of the gram-negative aerobic bacteria and fungi were reported to have been eliminated in the oral cavity and pharynx. 51 A systematic review indicated that the use of non-absorbable topical antibiotics is effective in the prevention of respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…21,23 Other studies employed this method; the rates of intra-oral bacterial colonization and VAP were found to reduce in all patients. 2,51 In the long-term use of SOD, most of the gram-negative aerobic bacteria and fungi were reported to have been eliminated in the oral cavity and pharynx. 51 A systematic review indicated that the use of non-absorbable topical antibiotics is effective in the prevention of respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous studies described the incidence of lung infection within 48 hours after the admission and artificial airway placement as VAP. [2][3][4] The aspiration of oropharyngeal organisms into the distal bronchial lumen is one of the most important mechanisms in the development of VAP. 5,6 Intubation and critical illness reduce oral immunity, may be associated with mechanical injury of the mouth or respiratory tract, and increase the likelihood of dry mouth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…mong different complications, ventilatorassociated pneumonia (VAP) is the most common nosocomial infections (NIs) that occurs in the intensive care unit (ICU) and affects about 20% of ICU patients and 30% of patients with mechanical ventilation (1). Numerous references have described the incidence of lung infection within 48 hours after admission and artificial airway placement as VAP (2,3). On the other hand, others also consider the incidence of lung infection within the first 24 hours as VAP (4).…”
mentioning
confidence: 99%